Screening blood tests in members of the Israeli National Olympic team - Eliakim, A.; Nemet, D.; Constantini, N. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: Blood samples are frequently collected in elite athletes in order to screen for possible medical conditions that might affect their athletic performance. However, the extent of these blood screening programs is not known. METHODS: Blood samples were collected from all members of the Israeli National Olympic team (n=114; 75 males, 39 females, mean age 23.4+/-0.5 years) to screen for possible medical conditions that might affect their athletic performance. All the athletes participated in individual sports. Fasting, early morning blood was sampled from all the athletes during the early phases of the training season (period of relatively light training). Blood was collected for erythrocyte sedimentation rate, complete blood count, chemistry panel, lipid profile, and iron stores analysis. RESULTS: Fifteen athletes (13%; 9 females, 6 males) had low ferritin levels (<20 ng/ml) indicating decreased iron stores. Four of these athletes (3.5%) had overt iron deficiency anemia. Two other athletes had B12 deficiency anemia. Three athletes had elevated serum creatinine and urea. Surprisingly, elevated levels of cholesterol (>200 mg/dl) were found in 15 athletes (13%). Moreover, 24 athletes (21%) had mild low HDL-cholesterol levels. No electrolyte abnormalities were found. CONCLUSIONS: Evaluation of iron stores should be performed in elite athletes, due to the relatively high prevalence of depleted iron stores and iron deficiency anemia, which may affect their athletic performance. We suggest that renal function should be tested in athletes prior to the use of food supplements and/or medications that may interfere with their renal function. Further studies are needed to determine the benefits of screening tests in elite athletes.